The association between neutrophil percentage to albumin ratio and progression-free survival and overall survival in colorectal cancer patients: a retrospective cohort study - Hailun Xie; Hailun Xie; Lishuang Wei; Shuangyi Tang; Jialiang Gan; Jialiang Gan (Frontiers in Nutrition, 2025)
BackgroundThe neutrophil percentage-to-albumin ratio (NPAR) is a promising indicator for predicting outcomes in various cancers. However, its prognostic value in colorectal cancer (CRC) is still underexplored. This study aimed to investigate the relationship between NPAR and progression-free survival (PFS) as well as overall survival (OS) in CRC patients.MethodsWe conducted a retrospective cohort study involving 1,339 CRC patients who underwent surgical resection. The Kaplan-Meier method was utilized to plot survival curves for PFS and OS. Cox proportional hazards regression analysis assessed the relationship between NPAR and survival outcomes. The nomograms that included NPAR and other significant prognostic factors were developed to predict 1-, 3-, and 5-year survival rates.ResultsPatients with high NPAR (≥1.62) experienced significantly worse PFS and OS compared to those with low NPAR (<1.62) (PFS: 47.4% vs. 63.1%, p < 0.001; OS: 50.1% vs. 65.9%, p < 0.001). Compared to other relevant markers, NPAR exhibited strong prognostic predictive efficacy. Multivariate Cox regression analysis identified high NPAR as an independent predictor of poor PFS (hazard ratio [HR] = 1.671, 95% Confidence Interval [CI]: 1.142–2.444, p = 0.008) and OS (HR = 2.697, 95% CI: 1.761–4.130, p < 0.001). The NPAR-based nomograms demonstrated high predictive accuracy and received favorable evaluations in the internal validation cohort.ConclusionPreoperative NPAR is a promising indicator for predicting PFS and OS in CRC patients. The NPAR-based nomogram offers a practical tool for personalized survival prediction and may assist in clinical decision-making.